Prostatic acid phosphatase is required for the antinociceptive effects of thiamine and benfotiamine. - Julie K Hurt (Public Library of Science (PLoS), 2012)
Thiamine (Vitamin B1) is an essential vitamin that must be obtained from the diet for proper neurological function. At higher doses, thiamine and benfotiamine (S-benzoylthiamine O-monophosphate, BT)-a phosphorylated derivative of thiamine-have antinociceptive effects in animals and humans, although how these compounds inhibit pain is unknown. Here, we found that Prostatic acid phosphatase (PAP, ACPP) can dephosphorylate BT in vitro, in dorsal root ganglia (DRG) neurons and in primary-afferent axon terminals in the dorsal spinal cord. The dephosphorylated product S-benzoylthiamine (S-BT) then decomposes to O-benzoylthiamine (O-BT) and to thiamine in a pH-dependent manner, independent of additional enzymes. This unique reaction mechanism reveals that BT only requires a phosphatase for conversion to thiamine. However, we found that the antinociceptive effects of BT, thiamine monophosphate (TMP) and thiamine-a compound that is not phosphorylated-were entirely dependent on PAP at the spinal level. Moreover, pharmacokinetic studies with wild-type and Pap(-/-) mice revealed that PAP is not required for the conversion of BT to thiamine in vivo. Taken together, our study highlights an obligatory role for PAP in the antinociceptive effects of thiamine and phosphorylated thiamine analogs, and suggests a novel phosphatase-independent function for PAP.